Neuroinflammation: Microglia and T Cells Get Ready to Tango - Schetters, Sjoerd T. T.; Gomez-Nicola, Diego; Garcia-Vallejo, Juan J.; Van Kooyk, Yvette (Frontiers in Immunology, 2018)
In recent years, many paradigms concerning central nervous system (CNS) immunology have been challenged and shifted, including the discovery of CNS-draining lymphatic vessels, the origin and functional diversity of microglia, the impact of T cells on CNS immunological homeostasis and the role of neuroinflammation in neurodegenerative diseases. In parallel, antigen presentation outside the CNS has revealed the vital role of antigen-presenting cells in maintaining tolerance toward self-proteins, thwarting auto-immunity. Here, we review recent findings that unite these shifted paradigms of microglial functioning, antigen presentation, and CNS-directed T cell activation, focusing on common neurodegenerative diseases. It provides an important update on CNS adaptive immunity, novel targets, and a concept of the microglia T-cell equilibrium.